Keluarga, Konsep Diri, dan Risiko: Determinan Intensi Berwirausaha Bagi Mahasiswa Prodi Akuntansi - Mila Hariani; Mochammad Irfan (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
Unemployment occurs due to many factors, one of which is due to limited job opportunities. Many college graduates become unemployed because practically they want to become government employees or in other words become job seekers, not job creators. The purpose of this study was to examine the impact of family environment, self-concept, and risk taking tendencies on entrepreneurial intentions. The population of this study are students of the Accounting Study Program at a university in East Java. This study used 118 respondents as a sample. Data analysis used multiple linear regression. The results showed that the family environment, self-concept, and the tendency to take risks had a significant and positive role in accounting students on entrepreneurial intentions